To complete the square for the quadratic equation \( y = x^2 - 16x + 14 \), we follow these steps:
-
Identify and rearrange the quadratic terms: \[ y = x^2 - 16x + 14 \]
-
Complete the square:
- Take the coefficient of \( x \), which is \(-16\), divide it by 2 to get \(-8\), and then square it to get \(64\).
- Add and subtract \(64\) inside the equation: \[ y = (x^2 - 16x + 64) - 64 + 14 \]
-
Rewrite the quadratic as a perfect square: \[ y = (x - 8)^2 - 50 \]
-
Identify the vertex: The vertex form of a quadratic \( y = a(x-h)^2 + k \) shows that the vertex is at point \( (h, k) \). Here, \( h = 8 \) and \( k = -50 \), so the vertex is \( (8, -50) \).
Thus, the correct response is:
\((8, -50)\)